1988
DOI: 10.1017/s0950268800054340
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial antibodies in farmers in north-west England

Abstract: SUMMARYBecause of recent reports of abortion in farmers' wives following infection with ovine strains of Chlamydia psittaci during pregnancy, the distribution of chlamydial antibodies was studied in rural populations in north-west England, where endemic chlamydial infection with abortion is common in sheep.Immunoperoxidase assays with C. trachomatis and ovine C. psittaci showed no significant differences in either the frequency or titres of antibodies between sheep farmers and other types of farmer or non-farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In Northern Ireland about 21 clinically ill patients are diagnosed serologically each year and a survey carried out by the Northern Ireland Regional Virus Laboratory in 1986 showed that 16 of 341 patient blood samples (4 7 %) from all over Northern Ireland had antibody to PLGV antigen. The finding of 38 (11 1 %) of the 341 farmers with antibody shows that the prevalence of infection is greater in this group than in the general Northern Ireland population but is similar to the 13 % antibody prevalence of farmers in North-West England [19].…”
Section: Resultsmentioning
confidence: 51%
“…In Northern Ireland about 21 clinically ill patients are diagnosed serologically each year and a survey carried out by the Northern Ireland Regional Virus Laboratory in 1986 showed that 16 of 341 patient blood samples (4 7 %) from all over Northern Ireland had antibody to PLGV antigen. The finding of 38 (11 1 %) of the 341 farmers with antibody shows that the prevalence of infection is greater in this group than in the general Northern Ireland population but is similar to the 13 % antibody prevalence of farmers in North-West England [19].…”
Section: Resultsmentioning
confidence: 51%
“…Ireland with different animal stocks including poultry, cattle, sheep, pigs, goats and horses were tested for zoonotic diseases by Hobson and Morgan-Capner (1988) and Stanford et 171. (1990).…”
Section: Farmers In North West England With Sheep Only and Farmers Inmentioning
confidence: 99%